2001
DOI: 10.1006/dbio.2000.9994
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Epithelial and Mesenchymal Estrogen Receptor-α Mediates Effects of Estrogen on Prostatic Epithelium

Abstract: In combination with androgens, estrogens can induce aberrant growth and malignancy of the prostate gland. Estrogen action is mediated through two receptor subtypes: estrogen receptors alpha (ERalpha) and beta (ERbeta). Wild-type (wt) and transgenic mice lacking a functional ERalpha (alphaERKO) or ERbeta (betaERKO) were treated with the synthetic estrogen diethylstilbestrol (DES). DES induced prostatic squamous metaplasia (SQM) in wt and betaERKO but not in alphaERKO mice, indicating an essential role for ERalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
137
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(148 citation statements)
references
References 39 publications
9
137
0
2
Order By: Relevance
“…1 Weihua et al 2 demonstrated that 5a-androstane-3b,17b-diol (3bAdiol) is an endogenous ER b ligand. Cytochrome P450 (CYP) 7B1 and 3b-hydroxysteroid dehydrogenase (3b-HSD) are two enzymes that may determine the 3bAdiol levels available at the ER b and hence affect the regulation of prostate proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Weihua et al 2 demonstrated that 5a-androstane-3b,17b-diol (3bAdiol) is an endogenous ER b ligand. Cytochrome P450 (CYP) 7B1 and 3b-hydroxysteroid dehydrogenase (3b-HSD) are two enzymes that may determine the 3bAdiol levels available at the ER b and hence affect the regulation of prostate proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Serum T was determined using a T double antibody radioimmunoassay kit (Diagnostic System Laboratories, Inc., Webster, TX, USA). The lowest detectable T concentration is 2.0 pg ml 21 . Animals used in the hormone studies were approximately 3 months of age.…”
Section: Hormone Radioimmunoassaymentioning
confidence: 88%
“…A growing body of evidence has suggested that Prostate branching morphogenesis in FSP-ERaKO mice M Chen et al 552 estrogen signaling exerts a direct impact on prostate pathogenesis and cancer. 18,21,43,44 Previous studies from conventional ER KO mice revealed that ERa, not ERb, is the critical receptor to mediate the estrogens response in those processes. 7,8,19,21 To investigate the in vivo roles of ERb in mouse prostate development, the neo-ERbKO mouse model was applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations